2015
DOI: 10.1007/s00520-014-2571-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms in the 2 years following diagnosis of breast or gynaecologic cancer: prevalence, course and determinants of outcome

Abstract: Women are most vulnerable to anxiety and depression at diagnosis, with improvement over time. Morbidity rates are lower than reported elsewhere. Women with high neuroticism and a psychiatric history are at greatest risk for future morbidity after adjusting for confounders. Early identification of these women plus heightened surveillance or early referral to psychosocial services may protect against longer-term morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 42 publications
4
36
2
1
Order By: Relevance
“…Another reported that having received treatment for anxiety or depression before diagnosis of breast or gynaecological cancer predicted depression 12 months later but not anxiety. However, this variable predicted neither outcome at 18‐ nor 24‐month follow‐up . In the same study, being in treatment for anxiety or depression at the time of diagnosis predicted anxiety 12 and 18 months later and depression at 18 months, but neither outcome at 2 years .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Another reported that having received treatment for anxiety or depression before diagnosis of breast or gynaecological cancer predicted depression 12 months later but not anxiety. However, this variable predicted neither outcome at 18‐ nor 24‐month follow‐up . In the same study, being in treatment for anxiety or depression at the time of diagnosis predicted anxiety 12 and 18 months later and depression at 18 months, but neither outcome at 2 years .…”
Section: Resultsmentioning
confidence: 89%
“…However, this variable predicted neither outcome at 18‐ nor 24‐month follow‐up . In the same study, being in treatment for anxiety or depression at the time of diagnosis predicted anxiety 12 and 18 months later and depression at 18 months, but neither outcome at 2 years . The third paper to find an effect of distress assessed at baseline reported that premorbid psychiatric history (diagnoses unspecified) predicted severe trauma 15 months after surgery for breast cancer .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Doxorubicin, cyclophosphamide, and the combination of doxorubicin and cyclophosphamide did not alter locomotor activity relative to saline treatment [F (3,20)=0.32, P=0.81] (Fig. 2).…”
Section: Doxorubicin and Cyclophosphamide Do Not Affect Locomotor Actmentioning
confidence: 85%
“…This incidence rate of cancer patients is higher than the prevalence in the community (3-4%) [2]. Furthermore, the prevalence rate of anxiety is 18.1% in breast or gynaecologic cancer patients [3]. Wittmann et al reported that the rates of anxiety and depression were 20.5% and 16.8%, respectively [4].…”
Section: Introductionmentioning
confidence: 97%